1986
DOI: 10.1016/s0735-1097(86)80265-0
|View full text |Cite
|
Sign up to set email alerts
|

Healing after myocardial infarction in the dog: Changes in infarct hydroxyproline and topography

Abstract: Temporal changes in infarct collagen and left ventricular topography during healing after myocardial infarction were studied in 132 dogs with coronary artery ligation: 8 sham dogs and 13 with no infarction (controls) and 111 with infarction (3 at 1 day, 54 at 2 days, 25 at 7 days, 3 at 2 weeks, 9 at 4 weeks and 17 at 6 weeks). Myocardial hydroxyproline (a marker of collagen) was measured by spectrophotometry and pathologic infarct size, arteriographic occluded bed size and topography by computerized planimetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(81 citation statements)
references
References 26 publications
6
74
1
Order By: Relevance
“…On the other hand, this finding is consistent with prolonged scar formation in the myocardium. [6][7][8][9][10] The peak serum PIIINP values were significantly correlated to the estimated infarction sizes, based on sequential determination of serum LD and CK-MB. This correlation is in accordance with that between the rate of collagen deposition during the early stage of infarction healing (measured by tissue hydroxyproline content) and the infarction size, as demonstrated by Jugdutt et al 8 Collagen type III plays a dominant role in early granulation tissue formation (scars).…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, this finding is consistent with prolonged scar formation in the myocardium. [6][7][8][9][10] The peak serum PIIINP values were significantly correlated to the estimated infarction sizes, based on sequential determination of serum LD and CK-MB. This correlation is in accordance with that between the rate of collagen deposition during the early stage of infarction healing (measured by tissue hydroxyproline content) and the infarction size, as demonstrated by Jugdutt et al 8 Collagen type III plays a dominant role in early granulation tissue formation (scars).…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, the induction of reperfusion marks the rapid evolution of an inflammatory-like response of which interstitial edema is a substantial feature. In chronic MI, on the other hand, enlargement of the extracellular space is mostly the result of the relatively large collagen matrix 19 in the absence of myocardial edema. 20 These considerations explain our findings that DE is a feature of MI regardless of its age and that high SI in edema-sensitive T2-weighted imaging is a feature of acute but not chronic MI.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in a low mortality rate of 12%, but the infarct scar at 6 weeks was small (9.5% of left ventricular mass), in agreement with previous reports.242527,28,1 As noted previously,31 because the infarct scar contracts and compacts over the 6 weeks, an infarct that is about 19% of left ventricular mass 1 day after coronary ligation is roughly equivalent to 14% at 1 week and 10% at 6 weeks. 25 Nevertheless, in the untreated group, morphometric analysis and infarct mapping showed that the transmural extent at 6 weeks averaged 62%, and echocardiograms revealed infarct-zone akinesis and dyskinesis, expansion, thinning, and aneurysmal bulging and noninfarct-zone hypertrophy and expansion and larger cavity size. A limitation of our canine model is that the dog heart has a rich collateral supply, the infarct-related artery remained permanently ligated, and the noninfarct-related arteries probably remained open throughout infarct healing.…”
Section: Effect Of Duration Of Nitrate Therapymentioning
confidence: 88%
“…Seventy-five healthy mongrel dogs (weight, 16 to 29 kg) of either sex were instrumented through a left lateral thoracotomy under general anesthesia (sodium pentobarbital, 30 mg/kg IV), as described previously. 25 (11 control, 11 nitrate). The dogs were allowed free access to fluids, and no attempt was made to treat heart failure by fluid restriction or pharmacotherapy.…”
Section: Experimental Preparationmentioning
confidence: 99%